2016
DOI: 10.1093/aob/mcw119
|View full text |Cite
|
Sign up to set email alerts
|

Plant family identity distinguishes patterns of carbon and nitrogen stable isotope abundance and nitrogen concentration in mycoheterotrophic plants associated with ectomycorrhizal fungi

Abstract: These authors contributed equally to this work. Background and Aims Mycoheterotrophy entails plants meeting all or a portion of their carbon (C) demands via symbiotic interactions with root-inhabiting mycorrhizal fungi. Ecophysiological traits of mycoheterotrophs, such as their C stable isotope abundances, strongly correlate with the degree of species' dependency on fungal C gains relative to C gains via photosynthesis. Less explored is the relationship between plant evolutionary history and mycoheterotrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 87 publications
10
58
0
Order By: Relevance
“…The extent to which OMFs contribute to the support of mature photosynthetic orchids is still an open question and likely varies among species and habitats (Girlanda et al ., ; Sommer et al ., ; Selosse & Martos, ; McCormick & Jacquemyn, ; Liebel et al ., ; Hynson et al ., ). Fungi almost certainly play an important role during periods of vegetative dormancy, a widespread phenomenon where plants, including many orchids, fail to produce any aboveground tissues, but remain physiologically active, during one or more growing seasons (Shefferson et al ., , , , ; Shefferson, ).…”
Section: Effects Of Orchid Mycorrhizal Fungi Abundance On Orchidsmentioning
confidence: 97%
“…The extent to which OMFs contribute to the support of mature photosynthetic orchids is still an open question and likely varies among species and habitats (Girlanda et al ., ; Sommer et al ., ; Selosse & Martos, ; McCormick & Jacquemyn, ; Liebel et al ., ; Hynson et al ., ). Fungi almost certainly play an important role during periods of vegetative dormancy, a widespread phenomenon where plants, including many orchids, fail to produce any aboveground tissues, but remain physiologically active, during one or more growing seasons (Shefferson et al ., , , , ; Shefferson, ).…”
Section: Effects Of Orchid Mycorrhizal Fungi Abundance On Orchidsmentioning
confidence: 97%
“…After the pioneering work of Gebauer and Meyer () and Trudell et al (), many studies have applied stable isotope analyses to assess the trophic modes of plants (e.g. Bidartondo, Burghardt, Gebauer, Bruns, & Read, ; Abadie et al, ; Tedersoo, Pellet, Kõljalg, & Selosse, ; Zimmer et al, ; Hynson, Preiss, Gebauer, & Bruns, ; Johansson, Mikusinska, Ekblad, & Eriksson, ; Hynson, Schiebold, & Gebauer, ; Jacquemyn, Waud, et al, ). Bidartondo et al (), for example, analysed isotope signatures in several orchid species inhabiting forest habitats and showed that orchids that associated primarily with rhizoctonia fungi were not significantly enriched in 13 C, whereas orchids associated with ectomycorrhizal fungi showed both significant enrichment in 13 C and 15 N. Similarly, Hynson et al () showed evidence for mycoheterotrophy on ectomycorrhizal fungi in several species of the tribe Pyroleae.…”
Section: Trophic Modes: a Continuum From Autotrophy To Mycoheterotrophy?mentioning
confidence: 99%
“…Due to its cryptic manifestation, partial mycoheterotrophy has so far only been confirmed for over 20 species of Orchidaceae (Hynson et al, ; Schiebold et al, ), although it seems much more likely that many more orchid species, if not all, show evidence of partial mycoheterotrophy (Schiebold et al, ). Further evidence for partial mycoheterotrophy has been found in c. 8 species of Ericaceae (within Pyrola, Orthilia and possibly Chimaphila and Moneses ), a single species of Burmanniaceae ( Burmannia coelestis ), and has been suggested for Gentianaceae ( Bartonia virginica and Obolaria virginica ) (Cameron & Bolin, ; but see Hynson, Madsen, et al, ; Hynson, Weiss, et al, ).…”
Section: Multiple Origins Of Full Mycoheterotrophymentioning
confidence: 99%
“…In terrestrial communities, plant foliage forms the base of many food chains. Foliage isotope values vary across spatial and temporal scales depending on climate, disturbance, and nutrient availability (Amundson et al, 2003;Craine et al, 2009;Pardo and Nadelhoffer, 2010;Popa-Lisseanu et al, 2015;Moreno et al, 2016;Taki et al, 2017) and with physiological differences between plant species, including variation in photosynthetic pathways (Basu et al, 2015;Courty et al, 2015;Taki et al, 2017) and mycorrhizal associations (Evans, 2001;Craine et al, 2009;Hynson et al, 2016). At longer time scales changes in atmospheric baselines, climate, and habitat succession can all cause progressive change in foliage isotopic signatures (Evans and Belnap, 1999;FoxDobbs et al, 2007;Wang et al, 2007;Taki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%